ANALISIS KADAR LOGAM Fe DAN Mn PADA AIR MINUM DALAM KEMASAN (AMDK) DENGAN METODE SPEKTROFOTOMETRI SERAPAN ATOM - Nisah, Khairun; Nadhifa, Husniah (Department of Chemistry, Faculty of Science and Technology, UIN Ar-Raniry, 2020)
This study aims to determine the levels of iron (Fe) and Manganese (Mn) in bottled drinking water (AMDK) using the Atomic Absorption Spectrophotometry (AAS) method. The bottled water used was 2 samples. In this study, obtained levels of Fe metals in the two AMDK samples using the instrument were Ë‚0,0002 while the calculation was -0.0468 mg/L. And the Mn metal content in both AMDK samples using the instrument was <0,0008 while the calculation was -0.0243 mg/L. The results of the analysis of Fe and Mn metals did not exceed quality standards stipulated by SNI 3553: 2015.